(untitled) (Research, Society and Development, 2022)
The aim of this study is to analyze insubordination in line with market orientation in restaurants. The methodology used was an exploratory and descriptive research, with a qualitative approach, created categories of analysis related to insubordination in restaurants and market orientation. Data collection took place through open questions using the data exhaustion technique with two restaurants called Restaurante Salmão and Pizzeria, as well as their main dishes, which were analyzed through content analysis. The main results show that it was possible to perceive that market orientation, mainly due to the responsiveness factor, fights insubordination, in addition, it is possible to verify with the employees hired through market orientation who demonstrates or not insubordination, with freelancers, did not show up. possible to check.